Utilization of Recycled Tiles and Tyres in Stabilization of Soils and Production of Construction Materials â A State-of-the-Art Review - Al-Bared, M.A.M. (Springer Verlag, 2018)
Tile waste is found in several forms including manufacturing slurry, manufacturing dust, and solid pieces from cracked, smashed, and rejected tiles at the construction sites. Worn out tyres that are no longer safe to be used by vehicles are either discarded or burned, adversely impacting natural ecosystems. These wastes are non-degradable and have a direct environmental impact. Poor waste management can lead to hazardous pollution, reduced soil fertility, and increased space consumption at disposal sites. The massive and increasing volume of the tile and tyre wastes calls for recycling of the materials for economical reuse, cleaner production, and greener development. One area for beneficial reuse of these waste materials is the improvement of engineering properties in soft soil. Structures on soft soils may experience several forms of damage due to insufficient bearing capacity and excessive settlement. Hence, soil stabilization is often necessary to ensure that the soft soil can meet the engineering requirements for stability. A comprehensive review of the published literature on the use of recycled tyres and tiles to stabilize and enhance soft soils was carried out. The properties of soft soil-waste mixtures such as liquid limit, plastic limit, plasticity index, compaction behaviour, unconfined compressive strength, and California Bearing Ratio have been presented. When used as partial replacement of cement, sand, and aggregate in concrete, the effect of tyre and tile waste on workability, durability, and compressive strength of the concrete has also been presented. Recycled tiles and tyres have been used with or without any other admixtures to sustainably improve the strength and bearing capacity of soil. The suitability of recycled tiles and tyres in soil stabilization has been discussed with regard to enhancement of strength and reduction of settlement. In addition, the beneficial effects of the recycled tiles and tyres, when they partially replace cement, sand or stone in concrete, have been discussed. Â© 2018 Korean Society of Civil Engineers